The complement control protein homolog of herpesvirus saimiri regulates serum complement by inhibiting C3 convertase activity. - Fodor, W L (1995)
The herpesvirus saimiri genome encodes a complement control protein homolog (CCPH). Stable mammalian cell transfectants expressing a recombinant transmembrane form of CCPH (mCCPH) or a 5'FLAG epitope-tagged mCCPH (5'FLAGmCCPH) conferred resistance to complement-mediated cell damage by inhibiting the lytic activity of human serum complement. The function of CCPH was further defined by showing that the mCCPH and the 5'FLAGmCCPH transfectants inhibited C3 convertase activity and effectively reduced cell surface deposition of the activated complement component, C3d.